Jesus in Asia - Sugirtharajah, R. S. (Rasiah S.) (Harvard University Press, 2018)
Reconstructions of Jesus occurred in Asia long before the Western search for the historical Jesus began in earnest. Asians remade Jesus at times appreciatively and at other times critically. R. S. Sugirtharajah situates the historical Jesus beyond the narrow confines of the West and offers an eye-opening chapter in the story of global Christianity.--Provided by publisher.